North+Lone Star Supernova Host Survey. I. Local Host-galaxy Hα Surface Brightness and the Hubble Residuals of Type Ia Supernovae - Ann M. Isaacs; Patrick L. Kelly; J. Craig Wheeler (The Astrophysical Journal)
We present optical integral field unit spectroscopy acquired with the George and Cynthia Mitchell Spectrograph on the Harlan J. Smith telescope at McDonald Observatory of 94 galaxies (0.01 < z < 0.058) that have hosted Type Ia supernovae (SNe Ia). We selected host galaxies with star-forming morphology, consistent with the criteria used by A. G. Riess et al. We measured the H α surface brightness (SB) of each host galaxy within 1 kpc of the location of the supernova. Using distances from the Pantheon+ sample, we find a step in Hubble residuals (HRs) compared to local H α SB of −0.097 ± 0.051 mag at 1.9 σ significance in a sample of 73 host galaxies, where SNe in environments with smaller H α SB are, on average, less luminous after correction for light-curve shape and color. Almost all of the SNe in our sample were discovered by targeted surveys. Using an independent sample primarily from the untargeted Nearby Supernova Factory survey, M. Rigault et al. found a step of 0.045 ± 0.029 mag where SNe in passive environments are instead brighter, which is in 2.4 σ tension with our measurement. M. Rigault et al. designated SNe Ia with comparatively small HRs (<−0.1) and faint local H α SB (<log _10 (H α SB/(erg ^−1 s ^−1 kpc ^2 )) = 38.32) as the M _2 population. SNe that would be classified as M _2 are less highly represented in our sample (7% versus 21%). When we include an additional 12 early-type galaxies, the number of M _2 SNe is almost doubled, although the tension with the HR step measured by M. Rigault et al. persists at 1.7 σ .